WEIGHT LOSS BUT SPICED UP? REVIEW OF CAPSAICIN AND ITS ROLE IN OVERWEIGHT AND OBESITY TREATMENT - Karol Bartecki; Alicja Bury; Natalia Kraciuk; Małgorzata Piekarska-Kasperska; Katarzyna Krupa; Julia Błoniecka; Anna Daniel; Jan Kamiński; Kacper Jankowski (International Journal of Innovative Technologies in Social Science, 2025)
Background. Obesity has become a worldwide problem. In the last decades the population of obese adults has doubled and obese adolescents quadrupled. Currently companies focus on developing new therapeutic agents, but there are still some phytochemicals with anti-obesity properties which need to be properly evaluated.Aim. This study reviews the current knowledge about the potential use of capsaicin and its analogues, capsinoids, in treatment of overweight and obese people.Material and methods. The article is based on research of clinical trials and meta-analyses published on the PubMed databases in the last decade using the following keywords: capsaicin, obesity, overweight, chili pepper, TRPV1.Results. Currently available studies demonstrate the influence of capsaicin intake on metabolism. The increase in resting energy expenditure and activity and density of brown adipose tissue show that capsaicin mobilizes metabolism in overweight and obese subjects. The positive effects require prolonged time of supplementation. Published results are incoherent mostly due to small groups of participants, different dosages of capsaicin, focus on variant parameters and short time of observation.Conclusions. Capsaicin modulates and promotes metabolism in overweight and obese adults. To properly evaluate its role in treatment plans, more comprehensive studies are needed.